Buzz Group in ESP Class to Improve Students' Speaking Skills - Nine Febrie Novitasari; Dwi Taurina Mila Wardhani (Pioneer: Journal of Language and Literature, 2018)
Teaching strategy and media are two important factors that influence the success of teaching and learning process. The implementation of Buzz group method that are integrated with audio visual media is one example of the effective teaching strategies that can be used to teach speaking. Students taking ESP class at UNARS had difficulties with speaking skill because of their limited vocabularies. Thus, this research tried to see how if Buzz group implemented with audio visual media implemented to the students to mprove their speaking skill. This CAR was held in one cycle. The result showed that the strategy was effective in improving the students’ speaking skill.